Konstruksi Internalisasi Empati : Strategi Komunikasi Digital @prosemicolon dalam Literasi Kesehatan Mental Generasi Z - Holilah, Ilah; Purwanti, Eneng (Program Studi Komunikasi dan Penyiaran Islam Fakultas Dakwah UIN Sultan Maulana Hasanuddin Banten, 2026)
This study explores the construction of empathy internalization as a counter-narrative to digital toxicity, focusing on the Instagram account @prosemicolon. Utilizing Pierre Bourdieu's Theory of Practice, the research examines how digital communication strategies facilitate the deep absorption of mental health values among Generation Z. A qualitative case study was conducted, analyzing 117 posts and audience interactions from September 2021 to June 2024 through digital observation and in-depth interviews. Findings reveal that @prosemicolon achieves empathy internalization by integrating consistent aesthetic visuals with highly relatable personal narratives. This strategic synergy allows Gen Z to move beyond passive information consumption toward active internal adoption of mental health literacy. The study concludes that structured community-led digital communication is effective in fostering cognitive and affective internalization, transforming the digital arena into a sustainable 'safe space' for psychological empowerment.